Association of Functional Movement Screen and Y-balance test scores with injury in high school athletes - Lisman, P.; Hildebrand, E.; Nadelen, M.; Leppert, K. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to determine the association between functional movement screen (FMS) and Y-Balance Test (YBT) performance and lower extremity injury in a sample of male high school athletes. A total of 124 high school football (n = 89), lacrosse (n = 25), and baseball (n = 10) players underwent FMS and YBT before the start of their competitive seasons. Time loss lower extremity injury incidence data were tracked by each team's certified athletic trainer and used for analysis. Receiver operating characteristic (ROC) curves were calculated to determine the optimal cutpoints for FMS composite score (CS) and YBT measures, including CS and reach distance asymmetry for anterior, posteromedial, and posterolateral directions, for predicting injury. No cutpoints on the ROC curves maximized sensitivity and specificity; therefore, FMS CS and YBT measures (CS and asymmetry) were analyzed as continuous variables. Logistic regression models adjusted for age and sport revealed no significant associations between FMS CS and lower extremity injury (odds ratio [OR] = 0.99; 95% confidence interval [CI] = 0.83-1.20). Similar findings were found for YBT asymmetry in all directions (ORs ranged from 0.98 to 1.08) and CS (OR = 0.99; 95% CI = 0.95-1.04). There were also no significant associations between the presence of asymmetry and low score (score of 1) on any individual FMS test and injury. Overall, FMS and YBT were not associated with increased risk of lower extremity injury in this sample of high school athletes. These findings do not support the use of FMS and YBT as stand-alone injury risk assessments in high school athletes.